The use of "CALL" to overcome shortage of English teachers / Edlin Ishak - Ishak, Edlin (2001)
The main aim of this study is to find out whether Computer Assisted Language Learning (CALL) can provide a solution to the shortage of English teachers, specifically in the Malaysian context. This study also seeks the perception of students towards CALL, as this aspect will contribute to determine whether the implementation of CALL in schools succeeds or fails. The instruments used in this study were both questionnaires and personal interviews. All the data were collected, categorized and analyzed. The findings revealed that CALL can provide a solution to the shortage of English teachers. Its capability to present lessons, as well as providing feedback and its interactivity captured the students' attention and consequently, favoured the use of CALL in classrooms. The interviews reported a significant opinion regarding the use of CALL as a solution to the problem mentioned. This study too, highlighted several foreseen problems in the implementation of CALL, which will defeat the purpose of having CALL in classrooms, as well as solving the problem of teachers’ shortage.